Effect of Overlapping Feeding on the Growth and Survival of Nilem (Osteochilus vittatus) Larvae - Risma Arafah Tunisa; Wiyoto Wiyoto; Cecilia Eny Indriastuti; Dian Eka Ramadhani; Riva Hafidah; Andri Iskandar; Robin Robin; Ikhsan Khasani (College of Vocational Studies, Bogor Agricultural University, 2025)
The nilem (Osteochilus vittatus) is an endemic freshwater species native to Indonesia and is valued both for its therapeutic properties and its potential for processing into value-added products such as baby fish chips. However, its relatively low growth rate remains a major constraint in aquaculture development. The effect of overlapping feeding on the growth performance and survival of nilem larvae was evaluated. Spawning was conducted over three periods using hormone-induced broodstock prior to larval rearing, and fertilized eggs were incubated under controlled conditions. Larval rearing was carried out at the Freshwater Fish Germplasm Research Installation using two feeding treatments with two replicates: a non-overlapping feeding regime, in which Infusoria was administered from day 4 to 7 followed by artificial feed, and an overlapping regime, in which Infusoria was provided from day 3 to 10 alongside artificial feed from day 8 to 10 before transfer to outdoor concrete tanks. Higher absolute weight gain (0.022 ± 0.001 g), absolute length gain (0.78 ± 0.03 cm), specific growth rate (3.30 ± 0.135%), and survival rate (90.0 ± 0.89%) were recorded under overlapping feeding compared to the non-overlapping treatment (0.018 ± 0.001 g; 0.67 ± 0.01 cm; 2.76 ± 0.111%; and 86.1 ± 0.62%, respectively). Significant differences (p<0.05) were observed in absolute length gain and survival, while absolute weight gain and specific growth rate were not significantly affected. Overlapping feeding was demonstrated to improve larval performance and can be recommended as a feeding strategy to enhance hatchery productivity in nilem aquaculture.